2006
DOI: 10.1111/j.1530-0277.2006.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Nerve Growth Factor in the Pathogenesis of Alcohol Dependence

Abstract: Our study suggests that the NGF levels may be a trait marker for the development of alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Furthermore, our results show a decreased serum NGF levels in the alcohol-dependent patients when compared to the healthy controls. Decreased plasma NGF concentrations in alcohol-dependent patients have been found before [23]. Our finding of a NGF decrease during alcohol withdrawal is in line with previous data on NGF plasma levels in alcohol-dependent patients showing a significant NGF plasma levels decrease from day 0 to day 7 during alcohol withdrawal [24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, our results show a decreased serum NGF levels in the alcohol-dependent patients when compared to the healthy controls. Decreased plasma NGF concentrations in alcohol-dependent patients have been found before [23]. Our finding of a NGF decrease during alcohol withdrawal is in line with previous data on NGF plasma levels in alcohol-dependent patients showing a significant NGF plasma levels decrease from day 0 to day 7 during alcohol withdrawal [24].…”
Section: Discussionsupporting
confidence: 82%
“…After chronic exposure to ethanol, a decrease of NGF had been observed in rats [22] and plasma. NGF concentrations in alcohol-dependent patients are significantly lower than in healthy controls [23]. Recently, Lee et al [18] demonstrated that the mean plasma NGF level was significantly higher in patients with alcohol dependence than in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotrophic factor nerve growth factor was reported to be involved in the pathogenesis of alcohol dependence (Yoon et al, 2006). Brain-derived neurotrophic factor (BDNF) is one of the most abundant neurotrophic factors in the brain (Chao, 2003), and it may be involved in the development of alcohol dependence.…”
mentioning
confidence: 99%
“…Indeed, authors discussed that withdrawal from chronic alcohol consumption may elicit significant stress and related anxiety triggering NGF blood release as previously observed for other stressing conditions [11,17]. However, other data showed lowered NGF levels in alcohol-dependent patients [26,49,50]. In one of these study alcoholics were abstinent for 30 days or longer to ruled out alcohol withdrawal effects such as anxiety [49].…”
Section: Discussionmentioning
confidence: 94%
“…In one of these study alcoholics were abstinent for 30 days or longer to ruled out alcohol withdrawal effects such as anxiety [49]. Thus it may be hypothesized that different circulating BDNF/NGF levels due to withdrawal or long-lasting abstinence or dependence or intoxication may reflect a trait marker of alcohol addiction rather than a state marker [26,28,49,51,52].…”
Section: Discussionmentioning
confidence: 99%